2020
DOI: 10.3390/ijerph17155420
|View full text |Cite
|
Sign up to set email alerts
|

High Boredom Proneness and Low Trait Self-Control Impair Adherence to Social Distancing Guidelines during the COVID-19 Pandemic

Abstract: Social distancing during the coronavirus-disease-2019 (COVID-19) pandemic is crucial to reduce the spread of the virus. However, its effectiveness hinges on adherence by individuals who face substantial burdens from the required behavioral restrictions. Here, we investigate sources of individual variation in adhering to social distancing guidelines. In a high-powered study (N = 895), we tested direct and indirect effects of boredom and self-control on adherence. The results showed that both traits were importa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 42 publications
11
108
2
3
Order By: Relevance
“…In addition, the generation of boredom is often accompanied by the appearance of various negative emotions, such as depression and anxiety, that severely affect people's mental state (Zhou et al, 2012). In terms of pandemic prevention and control, individuals who are high in boredom have been shown to have lower compliance with the quarantine policy and a higher likelihood of contracting COVID-19, which has been verified in samples from North America and Europe (Boylan et al, 2020;Wolff et al, 2020). Therefore, it is vital to explore strategies for coping with boredom during the pandemic quarantine period.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the generation of boredom is often accompanied by the appearance of various negative emotions, such as depression and anxiety, that severely affect people's mental state (Zhou et al, 2012). In terms of pandemic prevention and control, individuals who are high in boredom have been shown to have lower compliance with the quarantine policy and a higher likelihood of contracting COVID-19, which has been verified in samples from North America and Europe (Boylan et al, 2020;Wolff et al, 2020). Therefore, it is vital to explore strategies for coping with boredom during the pandemic quarantine period.…”
Section: Introductionmentioning
confidence: 91%
“…If the boredom during the quarantine is not well alleviated then the result seems to be serious. Compliance with the quarantine policy is positively correlated with self-control ( Wolff et al, 2020 ), individuals with low self-control are more likely to be bored ( Struk et al, 2016 ; Isacescu et al, 2017 ; Danckert et al, 2018a ; Isacescu and Danckert, 2018 ; Mugon et al, 2018 ), which makes them more likely to break the quarantine rules ( Boylan et al, 2020 ). Therefore, it is meaningful to explore appropriate boredom coping strategies during the quarantine.…”
Section: Introductionmentioning
confidence: 99%
“…All this implies that a certain degree of psychological well-being must be attainable to manage the situation ( Kanekar and Sharma, 2020 ). In other words, some amount of positive emotionality is needed to avoid falling into apathy or reactive depression, which are predisposed by such situations ( Wolff et al, 2020 ). For this reason, resilience as a personal characteristic, attitude or first-order skill becomes essential, as do personal character strengths ( Barzilay et al, 2020 ).…”
Section: Epidemiological Vs Behavioral Analysis For Prevention Durimentioning
confidence: 99%
“…For example, Zacher and Rudolph (2020) found that perceiving this pandemic as more health threatening resulted in life dissatisfaction and emotional instability two months later. In contrast, emotional stability and self-control are associated with less stress during this pandemic (Flesia et al, 2020), and self-control is also associated with greater adherence to social distancing guidelines (Wolff et al, 2020). Drawing from regulatory focus theory (Higgins et al, 2001(Higgins et al, , 2001), these reactions are likely dependent upon which needs are more salient.…”
Section: Motives For Security and Pleasurementioning
confidence: 99%